2020
DOI: 10.1016/j.envpol.2020.115072
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a century of mining and industrial production on metal contamination of a model saline ecosystem, Great Salt Lake, Utah

Abstract: Effects of mining and metals production have been reported in freshwater lake sediments from around the world but are rarely quantified in saline lake sediments, despite the importance of these lake ecosystems. Here we used dated sediment cores from Great Salt Lake, Utah, USA, a large saline lake adjacent to one of the world's largest copper mines, to measure historical changes in the deposition of 22 metals. Metal concentrations were low prior to the onset of mining in the catchment in 1860 CE. Concentrations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 76 publications
(93 reference statements)
0
4
0
Order By: Relevance
“…With respect to the presence of copper in the environment, it is well known that the mining and production of this metal can mean various adverse impacts [14][15][16][17] . These impacts include-among others-water and soils pollution, and emissions of greenhouse gases [18][19][20][21][22][23] .…”
Section: Copper Into the Environmentmentioning
confidence: 99%
“…With respect to the presence of copper in the environment, it is well known that the mining and production of this metal can mean various adverse impacts [14][15][16][17] . These impacts include-among others-water and soils pollution, and emissions of greenhouse gases [18][19][20][21][22][23] .…”
Section: Copper Into the Environmentmentioning
confidence: 99%
“…S2L), which likely yields extensive ecological effects at multiple trophic levels (44). Samples collected from site 6 were particularly high in arsenic content, which can be attributed to that site's relative proximity to mining and smelting activities (45). Taken together, the GSL-nematode microbiome contains several members with known mechanisms of energy production, hypersaline tolerance, and toxic-chemical resistance.…”
Section: The Microbiome Of Great Salt Lake Nematodes Hints At Co-evol...mentioning
confidence: 99%
“…4 Regional differences of the EFs of metals in surface sediments across the CACs which is not only related to industrial and agricultural activities but has also been connected to the high background value for Zn in the region. Here we took core sediments from lake bottoms as background references in local regions (Lin et al 2016;Wurtsbaugh et al 2020;Yu et al 2021), and the average concentration of Zn in the CACs was up to 51.3 mg kg −1 (Table S4), which significantly exceeded the background level for sediments from around the world (9 mg kg −1 ) (Table S4). Moreover, studies have shown that Zn contents in rivers of mountainous regions are also relatively high (Groll et al 2015;Zhang et al 2020).…”
Section: Enrichment Assessment and Regional Differencementioning
confidence: 99%